Harmony of national cognition and world perception (Eurasian Journal of Philology Science and Education, 2022)
The article provides an overview of the first book of the documentary historical story of M. Magauin «Genghis Khan» and analyzes the common conditions of Turkic cognition. In particular, the history and culture of the nation, the personality of the leader of the nation, his place in history are analyzed, and the author’s study of genealogical and documentary channels is proved by examples. If we pay attention to the researches and traces of M. Magauin, the writer through the historical story «Genghis Khan» introduced Genghis Khan, and particularly the Turkic community to the world. One of the most important issues is to create a personal image of the great commander, his heroism, his artistic image as a citizen. The fundamental research of many scientists on the spirituality of the nation, the commander-in-chief, is reflected in a positive way. The author’s assimilation of historical themes, methods and techniques of transforming the reality of life into an artistic reality, and the aspects of their implementation are comprehensively analyzed. The image of the protagonist, the meaning of words in the text, the continuity of time, the plot are reflected in the modern scenes. The main ideas of the author’s position on humanity in the struggle of good and evil are discussed in detail in this article.